Challenges and Opportunities of Promoting Complementary and Alternative Medicine (CAM) in Iran's Internet Arena. Issue 2 (3rd April 2018) - Aghaei, Atefeh; Khalili, Mohsen
ABSTRACT: Promoters of complementary and alternative medicine (CAM) increasingly benefit from the use of the Internet. The purpose of this article is to study the barriers and opportunities facing the promotion of complementary and alternative medicine in Iran's Internet space. The main research questions are: What are the obstacles encountered in Iran while using the Internet to promote CAM? What opportunities are available for promoting CAM on the Internet? How did Iranian users interact with complementary and alternative Internet sites? In the study, 24 executives of CAM websites in Iran were interviewed; executives were selected through purposive sampling. According to the findings, the greatest opportunity provided by the Internet in Iran is "the Internet as a new arena to compete with modern medical discourse." Yet, barriers to engaging in the Iranian Internet include "obstacles related to different ways of users' presence, " "obstacles to CAM site management, " "obstacles caused by Iran's Internet regulations, " and "the dominance of modern medical discourse even on the Internet." Thus, the Internet has provided an opportunity to challenge modern medical discourse in Iran, but due to the specific conditions of Iran's Internet, there are still many limitations to the presence of competing medical discourses on the Internet.